Regional Cooperation Among Indian Ocean Countries (Rawalpindi, Pakistan A Friends Publication, 1999)
Papers read at an International Seminar on Regional Cooperation Among Indian Ocean Countries, held in Islamabad.
Include Maps and Appendix
Keywords: Indian Ocean Region -- Politics and government -- Economic history -- International economic integration